Load Carrying Analysis for Turning Arm Bearings of Cycloidal Gear Reducers with Manufacturing Errors - Wei Shixiong; Yang Jianjun; Wei Bingyang; Wang Yongqiang; Xu Jiake (Jixie chuandong)
The bearing performance and wear condition of the turning arm bearing of cycloidal reducers are closely related to the rotary accuracy and life of reducers. Aiming at the actual wear condition of a 150BX type cycloidal reducer bearing hole, first of all, the bearing model of the turning arm bearing was established, and the change rules of the maximum load and its direction were established. Then the motion models of the cycloidal gear and crankshaft containing manufacturing errors were established, the interference of the manufacturing errors on the movement of the turning arm bearing was analyzed, and the maximum interference position on the turning arm bearing and the error selection method were obtained. The findings of this study provide a basis for the wear calculation of the turning arm bearing of the cycloidal reducer and the error selection of key components.